Centrifugal Differential Mobility Analysis—Validation and First Two-Dimensional Measurements - Rüther, Torben Norbert; Gröne, Sebastian; Dechert, Christopher; Schmid, Hans-Joachim (Powders)
To obtain a more comprehensive understanding of the specific properties of complex-shaped technical aerosols—such as partially sintered aggregates formed in combustion processes or structured particles resulting from complex synthesis processes—it is essential to measure more than a single equivalent size. This study examines a novel method for determining a two-dimensional distribution of two distinct particle properties within the size range from 50nm to 1000nm: the Centrifugal Differential Mobility Analyzer (CDMA). The CDMA enables the simultaneous measurement of both mobility and Stokes equivalent diameters, providing a detailed two-dimensional particle property distribution. This, in turn, allows for the extraction of shape-related information, which is essential for characterizing particles in terms of their chemical composition, reactivity, and other physicochemical properties. This paper presents a detailed evaluation of a first CDMA prototype. First, CFD simulations of the flow field within the classifier are presented in order to assess and understand non-idealities arising from the exact geometry. Subsequently, the transfer function is evaluated by particle trajectory calculations based on the simulated flow field. It can be demonstrated that the simulated transfer functions agree quite well with transfer functions derived from streamlines of an ideal flow field, indicating that the non-idealities in the classifying region are almost negligible in their effect on the classification result. An experimental determination of the transfer function shows additional effects not covered by the previous simulations, like broadening by diffusion and losses due to diffusion and precipitation within the in- and outlet of the classifier. Finally, the determined transfer functions are used to determine the full two-dimensional distribution with regard to the mobility and Stokes equivalent diameter of real aerosols, like spherical particles and aggregates at different sintering stages, respectively.
Keywords: centrifugal differential mobility analysis; 2D-measurement; particle characterization; moving reference frame CFD-simulation; transfer function